EPIZOOTOLOGICAL FEATURES OF GOOSE TRICHOSTRONGYLOSIS DEVELOPMENT ON FARMS OF POLTAVA REGION - Starodub, Ye.; Melnychuk, V. (Scientific Progress & Innovations, 2020)
Infections caused by nematodes parasitizing in poultry gastrointestinal tract, including trichostrongylo-sis, are quite common among goose helminthiases. Trichostrongylus tenuis pathogen is localized in poultry’s cecum, less often – in the small intestine. The invasion causes a delay in growth and development of young poultry, negatively affects the productivity, product quality and functional activity of the immune system. The aim of the research was to establish the epizootological features of goose trichostrongylosis development on farms of Poltava region. According to the results of helminthological autopsies of domestic geese, it was found that the average prevalence of trichostrongylosis infestation in Poltava region made 27.54 % (fluctu-ating from 20.00 to 39.34 %, the intensity of the invasion – 13.09±0.95 specimens/head (fluctuating from 1 to 42 specimens/head). It was found that goose trichostrongylosis more often (81.55 % of infected poultry) oc-curred in the form of mixed invasions with nematodoses, cestodoses and trematodoses. Trichostrongylosis mono-invasion was found in 18.45 % of diseased poultry Mixed invasions were represented by two-, three-, four-, five- and six-component varieties. Invasions consisting of two species of parasites were dominant (the prevalence of infection made 10.43 %), where the co-members of Trichostrongylus tenuis were nematodes of the following species: Amidostomum anseris, Heterakis dispar, Baruscapillaria anseris, Baruscapillaria ob-signatica, cestodes of the species: Fimbriaria fasciolaris, Sobolevicanthus gracilis and trematodes of Echi-noparyphium aconiatum species. The prevalence of other types of mixed invasions ranged from 0.80 to 5.08 %. A total of 28 varieties of associative development of goose trichostrongylosis were identified, where 7 kinds were two-component, 14 – three-component, 5 – four-component, 1 – five-component, and 1– six-component. The main co-members of nematodes of Trichostrongylus tenuis genus in geese were H. dispar nematodes (prevalence of infection made 9.89 %), B. anseris (9.89 %) and A. anseris (6.68 %). Associations of trichostrongylus with H. conoideum (4.28 %), S. gracilis (3.74 %), F. fasciolaris (3.48 %), H. gallinarum (3.48 %) and B. obsignata (1.87 %) were less numerous.